2014
DOI: 10.3810/pgm.2014.10.2827
|View full text |Cite
|
Sign up to set email alerts
|

Delirium Superimposed on Dementia and Mild Cognitive Impairment

Abstract: Dementia is an illness that progressively affects cognition, emotion, and functional status. It can be complicated by delirium, an acute disturbance of consciousness and cognition that develops over a short course with fluctuating symptoms. Patients with dementia who experience delirium tend to have slower resolution of symptoms, more adverse events, and poorer outcomes. There are significant health care expenditures associated with delirium. Many health care providers fail to recognize and diagnose delirium. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…In a prospective cohort study of 101 non-ICU geriatric patients (aged ≥75 years), the authors reported that the 3D-CAM was superior than the CAM-ICU in diagnosing delirium [28]. Delirium assessment in patients with cognitive impairment or dementia is a challenging task [29]. Lack of an efficient instrument is considered the main reason of mis-and underdiagnosis of delirium in this population [29,30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a prospective cohort study of 101 non-ICU geriatric patients (aged ≥75 years), the authors reported that the 3D-CAM was superior than the CAM-ICU in diagnosing delirium [28]. Delirium assessment in patients with cognitive impairment or dementia is a challenging task [29]. Lack of an efficient instrument is considered the main reason of mis-and underdiagnosis of delirium in this population [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…Delirium assessment in patients with cognitive impairment or dementia is a challenging task [29]. Lack of an efficient instrument is considered the main reason of mis-and underdiagnosis of delirium in this population [29,30]. Marcantonio and colleagues [16] reported that the sensitivity and specificity of the 3D-CAM in dementia patients was 96% and of 86%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Both of these disorders increase each other’s risk of development [ 3 , 4 ] and are more common among the elderly [ 1 , 5 ]. Both delirium and dementia have a common pathological mechanism, which results in many similarities in the clinical presentation, creating additional diagnostic difficulties [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, delirium often goes underdiagnosed by clinicians and is frequently inadequately managed (Gower, Gatewood, & Kang, 2012; Press et al, 2009). It is probable that delirium is often overlooked or misdiagnosed (Farrell & Ganzini, 1995) because its recognition can be particularly difficult in older patients who often have physical and psychiatric comorbidities that may contribute to cognitive, affective, and/or behavioral changes (Gagliardi, 2008; Gonzalez, de Pablo, & Valdes, 2003; Kolanowski et al, 2015; Marchington, Carrier, & Lawlor, 2012; Roden & Simmons, 2014). Findings in a recent survey on family caregivers’ knowledge of delirium (Bull, Boaz, & Sjostedt, 2014) indicate that family caregivers appear to confuse symptoms of delirium with dementia, which illustrates that delirium symptom identification is a challenge across the continuum of care.…”
Section: Introductionmentioning
confidence: 99%
“…Findings in a recent survey on family caregivers’ knowledge of delirium (Bull, Boaz, & Sjostedt, 2014) indicate that family caregivers appear to confuse symptoms of delirium with dementia, which illustrates that delirium symptom identification is a challenge across the continuum of care. One case study suggests that the diagnosis of delirium is frequently missed or misdiagnosed as depression in patients with hypoactive forms of delirium because of the overlap in symptoms between the two diagnoses (Roden & Simmons, 2014).…”
Section: Introductionmentioning
confidence: 99%